Catarata congênita: aspectos diagnósticos, clínicos e cirúrgicos em pacientes submetidos a lensectomia - Oliveira, Márcia Lima Santos [UNIFESP] (2004)
PURPOSE: To analyze the clinical and therapeutic profiles of children with congenital cataract submitted to lensectomy. METHODS: Retrospective study of 89 eyes of 62 children who underwent surgery at the Congenital Cataract Sector - Department of Ophthalmology - Federal University of São Paulo, Brazil. RESULTS: Among the 62 children, 30.64% showed infectious causes, 19.36% genetic causes and 50% idiopathic causes. Strabismus was found in 54.83% of the patients and 27.42% had systemic diseases. Concerning pregnancy conditions, 22.58% of the mothers had no adequate prenatal care. Consanguinity was observed in 17.74% of the cases and congenital cataracts in 6 (9.68%) relatives. The diagnostic suspicion was of the mothers in 72.58% of children. Leukocoria was the main feature. The suspicion age varied from immediately after birth to 15 months (mean = 1.34 months). Age on diagnosis in the department varied from 8 days to 20 months (mean = 5.84 months). Secondary opacification in the visual axis was the most frequent postoperative complication; it occurred in 19.11% of 89 eyes. It was observed that 45.16% of the patients had difficulties in following postoperative treatment. They did not use eyeglasses, eye drops or correct eye patching for amblyopia. CONCLUSION: Rubeola is still one of the most important causes of congenital cataract in our country. This condition shows the necessity of better prevention. The first diagnostic suspicion is mainly by the mothers and within the three first months of age in most children, but there is a considerable delay between suspicion and the patient's presence in a specialized service center. Despite satisfactory surgery results, delay of surgery and difficulties in postoperative treatment impair final visual results.